2015
DOI: 10.1002/ppap.201570033
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Plasma Process. Polym. 9∕2015

Abstract: Front Cover: Spectroscopic investigations of plasma properties and polymer surface‐near regions reveal the oxidative degradation of polymer interface as a function of atomic oxygen fluence during deposition of silicon oxide films. The absolutely quantified atomic oxygen fluence is determined by means of optical emission spectroscopy. Self‐assembled monolayers are used to mimic an aliphatic polymer and to track the interfacial changes by PM‐IRRAS. The interface stays intact if the atomic oxygen fluence is kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[16] The application of FTIR spectroscopy for the analysis of the crosslink density and internal silanol (SiOH) dangling bonds in thin SiO x films could be performed by evaluating the intensity of the absorption signal for silanol groups or directly by analysing the absorption band of the asymmetrical Si-O-Si stretching mode in the range of 900 and 1350 cm -1 . The asymmetrical Si -O-Si stretching mode shows a split into longitudinal (LO) and transverse (TO) modes, which can be, as shown earlier, [14,16,18] can be used as markers for the internal structure.…”
Section: Introductionmentioning
confidence: 62%
“…[16] The application of FTIR spectroscopy for the analysis of the crosslink density and internal silanol (SiOH) dangling bonds in thin SiO x films could be performed by evaluating the intensity of the absorption signal for silanol groups or directly by analysing the absorption band of the asymmetrical Si-O-Si stretching mode in the range of 900 and 1350 cm -1 . The asymmetrical Si -O-Si stretching mode shows a split into longitudinal (LO) and transverse (TO) modes, which can be, as shown earlier, [14,16,18] can be used as markers for the internal structure.…”
Section: Introductionmentioning
confidence: 62%
“…Further investigations regarding the influence of the atomic oxygen produced during film deposition on the substrate have been conducted by Mitschker et al [75] The authors used different O 2 -HMDSO ratios thereby varying the atomic oxygen fluence the substrate is exposed to during deposition. In addition to the decay of the ODT-SAM characteristic peaks as reported by Ozkaya et al, [74] a shift of the Si-O-Si (LO) peak toward F I G U R E 11 Left: Survey on a typical plasma-enhanced atomic layer deposition (PEALD) process sequence consisting of (1) the precursor pulse, (2) an inert gas purge, (3) the plasma pulse, and (4) another purge sequence.…”
Section: Molecular Understanding Of Interface Processesmentioning
confidence: 99%
“…Further investigations regarding the influence of the atomic oxygen produced during film deposition on the substrate have been conducted by Mitschker et al [ 75 ] The authors used different O2 ${{\rm{O}}}_{2}$‐HMDSO ratios thereby varying the atomic oxygen fluence the substrate is exposed to during deposition. In addition to the decay of the ODT‐SAM characteristic peaks as reported by Ozkaya et al, [ 74 ] a shift of the Si–O–Si (LO) peak toward higher wavenumbers was observed for increasing atomic oxygen fluence.…”
Section: Nucleation and Thin Film Growthmentioning
confidence: 99%
“…During the first stages of growth, volatile fragments etched from the substrate surface as a result of plasma exposure are known to intermingle with the growing SiO x structure, leading to the formation of an interphase whose characteristics are still not fully understood. The structure and properties of this interphase play, however, a central role in determining the further evolution of the SiO x film in terms of nanometre‐scale defect formation and overall structure, which are key features for the development of a good barrier against gas permeation . Therefore, trying to elucidate the growth mechanisms at the initial growth stages has been the subject of several studies, in spite of which it is still a matter of discussion as to what growth mode SiO x thin films adopt.…”
Section: Introductionmentioning
confidence: 98%